2012
DOI: 10.1016/j.chroma.2012.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of new superficially porous particles

Abstract: Superficially porous particles (also called Fused-Core, core shell or porous shell particles) show distinct advantages over comparable totally porous particles for separating small molecules. Columns of Fused-Core particles exhibit very high efficiency because of superior eddy dispersion properties (smaller van Deemter A term). The efficiency for columns of 2.7 μm Fused-Core particles actually rivals that for sub-2 μm totally porous particles with only about one-half the back pressure. These Fused-Core particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 22 publications
(30 reference statements)
5
64
0
Order By: Relevance
“…In general, studies have suggested a compromise between a short diffusion path (which leads to high efficiency) and adequate retention / mass load tolerance. Shell particles with thinner porous shells show marginal improvement in column efficiency for small molecules, but improved performance for larger molecules which have much smaller diffusion coefficients and thus give higher mass transfer contributions to band broadening 59 . This particular study indicated the best compromise for large molecules was a 0.2 m shell thickness.…”
Section: Effect Of Shell Thickness and Of Pore Size On Performance mentioning
confidence: 99%
“…In general, studies have suggested a compromise between a short diffusion path (which leads to high efficiency) and adequate retention / mass load tolerance. Shell particles with thinner porous shells show marginal improvement in column efficiency for small molecules, but improved performance for larger molecules which have much smaller diffusion coefficients and thus give higher mass transfer contributions to band broadening 59 . This particular study indicated the best compromise for large molecules was a 0.2 m shell thickness.…”
Section: Effect Of Shell Thickness and Of Pore Size On Performance mentioning
confidence: 99%
“…Wu and Clausen [12] demonstrated that use of all silica particles with smaller diameter to achieve efficient separation always leads to increased back pressure. DeStefano et al [13] have shown that as particle size of superficially porous silica decreases, column efficiency increases but the operating pressure increases drastically as a square of the particle size. Unger et al demonstrated that halving the particle size may double separation performance (in terms of column efficiency or theoretical plate numbers), and http://dx.doi.org/10.1016/j.chroma.2015.04.034 0021-9673/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we investigated the accuracy of prediction of gradient data in fast gradient chromatography (1−2 min) on short columns packed with fully porous [2] or superficially porous (core−shell) particles [3,4] with different chemistries of bonded stationary phases. We found that either 5 or 3 cm core-shell columns may provide comparable peak capacity in a fixed short gradient time with optimized gradient range.…”
Section: Introductionmentioning
confidence: 99%